(Im)politeness strategies, power and gender relations in Philippine romantic films - Garcia, Georgina R.; Lustre, Anna Francesca A.; Pancho, Richmon M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2011)
Brown and Levinson's politeness theory and Culpeper's impoliteness theory have been employed numerous times in foreign studies. The researchers have found out, through this study, that these can also be used to analyze texts in the local context. This study focuses on five top-grossing Philippine romantic films, namely, Kasal, Kasali, Kasalo, One More Chance, For the First Time, Miss You Like Crazy and A Very Special Love. The date has been limited to encompass only the arguments between the lead male and female characters in these films. Aside from the aforementioned politeness and impoliteness strategies, the researchers have chosen to observe the different gender and power relations present among the couples. These films contexts are then situated in Metro Manila Cosmopolitan Context. Results from this study show that the power relations between the lead male and female characters depend on the pursuer and the pursued in the relationship. The pursuer, who are often the males, shows a lower relative power as compared to the pursued, who are often the females, as the former tries to maintain the romantic relationship while the latter resists it. The pursued shows a tendency to use more impoliteness strategies, specifically bald-on record and positive impoliteness. The pursuer, on the other hand, generally uses more politeness strategies which concentrated on positive and off-record politeness. The main usage of the off-record politeness strategy and the bald on-record impoliteness strategy reflect the Filipino culture's concept of saving face through indirect utterances. Additionally, the major usage of politeness and impoliteness strategies that are oriented towards the positive face illustrate the Filipino's concept of self and kapwa.
Thesis (B.A. in English Studies)
Keywords: Romance films -- Philippines; Politeness (Linguistics); Romance-language drama -- Philippines